Looking up and going down: Does sustainable adaptation to climate change ensure dietary diversity and food security among rural communities or vice versa? - Haq, Shamsheer ul; Shahbaz, Pomi; Abbas, Azhar; Alhafi Alotaibi, Bader; Nadeem, Nasir; Nayak, Roshan K. (Frontiers in Sustainable Food Systems, 2023)
Sustainable food systems are essential to ensure food security and mitigate climate change. Adaptation to climate change is part and parcel of sustainable food systems. Prior literature merely documented the climate-smart agricultural practices and explored the relationship with food security of adopters without taking the period of the strategies into account. Therefore, this study explored the factors affecting sustainable adaptation to climate change and created a further link between sustainable adaptation to climate change and the food security of rural households. The cross-sectional data were collected from 384 farmers through a face-to-face survey in Pakistan, selected by a multistage random sampling method. An ordered probit model and propensity score matching technique were used to analyze the data. Education, farm size, credit access, extension services, internet use for agriculture information, women's participation in farm-related decision making, and considering climate change a significant problem for agriculture were all positively influencing the sustainable adaptation to climate change at farms. The results indicated that farmers with a higher level of sustainable adaptation to climate change consumed more diversified diets and more daily calories as compared to those with a lower level of sustainable adaptation. Similarly, farmers with a lower level of sustainable adaptation to climate change had significantly lower food security than farmers with a high level of sustainable adaptation at their farms. This research indicated that farmers can gain food and nutrition benefits by becoming more sustainable adapters to climate change. This study has important policy implications for achieving sustainable development goals (SDGs) of zero hunger (SDG 2) and climate action (SDG 13) in developing countries.